Managing immigration in the 21st century - Barry R. Chiswick (Institute for the Study of Labor (IZA), 2015)
In this paper I share my thoughts on immigration policy. As a social scientist it is appropriate to assess the consequences, the costs and benefits, of alternative immigration policies. The policies that a country adopts regarding immigration, however, should be the outcome of a political process which should be informed by, but not dictated by, social science research. What follows is a non-technical discussion of what I see as some of the key issues regarding immigration policies currently facing the United States and other technologically advanced economies.
Keywords: F22; 330; immigration; immigrants; immigration policy; skilled and low-skilled workers